Photodynamic therapy for cervical lesions - E. V. Grebenkina; S. V. Gamajunov; S. S. Kuznetsov; O. V. Onoprienko; N. A. Illarionova; N. M. Shakhova (Biomedical Photonics)
The experience of treatment for precancer and early cervical cancer by photodynamic therapy in 12 patients with primary diagnosis H-SIL (CIN II–III) and cancer in situ is described. Chlo-rine photosensitizer Photolon was given intravenously at a dose of 0.75–1.15 mg/kg body weight. 2.5 h later the treatment with polyposition laser exposure (light dose – 150 J/cm2, light power density – 400–500 mW/cm2) was made. Thirty days later conization of the cervix with endocervical curettage assessing therapeutic response of cervical tumor tissue was per-formed. According to histological data complete response was in 4 patients, minute foci of CIN I were determined in 7 patients, 1 patient had foci of CIN II. 8 of 10 HPV-positive patients had complete eradication of HPV after treatment. There were no serious adverse events after light exposure. Marked therapeutic response, high anti-viral activity and good feasibility allow to consider photodynamic therapy as alternative organ-sparing treatment of early cancer and pre-cancer of cervix.